Transforming the centre right in Germany and the United Kingdom: the increasing prominence of identity politics and “culture wars” narratives - Schmidtke, Oliver (Frontiers in Political Science, 2025)
This manuscript examines the transformation of centre-right politics in Germany and the United Kingdom, focusing on how “culture wars” rhetoric and identity politics have influenced the political strategies of the CDU (Christian Democratic Union) and the UK Conservative Party. It explores how these parties have responded to the rise of right-wing populism, prominently through the framing of cultural issues such as migration, national identity, and gender politics. While the UK Conservatives have embraced nationalist-populist rhetoric, especially during the Brexit campaign, the CDU has maintained a more policy-driven, pragmatic approach. The article argues that while identity politics can be a powerful tool for voter mobilization, it risks alienating moderates and deepening societal divisions. Reflecting on the impact of the “cultural wars” rhetoric on competitive party politics, the study highlights the challenge for centre-right parties in balancing the demands of an increasingly polarized electorate with the need to preserve their traditional policy-focused, moderate conservatism in the face of populist pressures.